Median Sacral Artery Rupture as a Complication of Posterior-Only Approach of L4 Total En Bloc Spondilectomy: A Case Report. Issue 3 (7th July 2020) - Garcia-Maya, Beatriz; Pizones, Javier; Sanchez-Marquez, Jose Miguel; Talavera, Gloria; Perez-Grueso, Francisco Javier; Fernandez-Baillo, Nicomedes
Abstract : Case: A 6-year-old patient with Ewing sarcoma at L4 who was treated with total en bloc spondilectomy (TES) through a posterior-only approach. During the dissection of the anterior L4 body, there was uncontrollable bleeding from an unknown origin, which needed packing, massive transfusion, and urgent laparotomy. A median sacral artery (MSA) rupture was identified as the cause of this massive bleeding. Eventually, the patient was successfully stabilized. Conclusions: To our knowledge, this is the first reported intraoperative bleeding of the MSA related to a lumbar TES through posterior-only approach. This life-threatening complication should be considered when planning for this type of surgery.